The Impact of Hospital Management Information Systems (HMIS) on Human Resource Efficiency and Effectiveness: A Literature Review - Nur Atifah; Oryza Sativa H Sihotang; Nur Indah Rahma Dilla; Khairizah Afifah; Firda Vinanda; Sri Hajijah Purba (Pancasakti Journal Of Public Health Science And Research, 2025)
The Hospital Management Information System (HMIS) is an information technology platform that integrates all service workflows in a hospital to obtain precise and accurate information. The use of HMIS is considered essential for improving healthcare service quality and hospital operational efficiency. This study aims to explore the impact of HMIS on the efficiency and effectiveness of human resource (HR) performance in hospitals. The research employs a literature review method, collecting data from various relevant sources such as journals, books, and online resources, primarily from the last five years (2020–2024). The implementation of HMIS in hospitals has demonstrated improvements in HR performance efficiency and effectiveness. HMIS facilitates better data management, enhances coordination among work units, and accelerates healthcare service processes. However, effective implementation heavily relies on management support, workforce readiness, and the availability of adequate technological infrastructure. Investments in HMIS not only enhance HR performance but also contribute to the overall improvement of service quality for patients.